Design and evaluation of a circuit-based team competition model to enhance fundamental athletic skills in primary school physical education - Iskandar; Juhanis; Mappaompo, M. Adam; Abdillah, M. Yusuf Susilo; Aliriad, Hilmy (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2025)
Background: Innovative learning models are essential for enhancing fundamental athletic skills among primary school students. Traditional methods often fail to engage learners, leading to low participation and limited skill development in physical education (PE). There is a need for engaging, structured models that effectively combine physical activity with motivation and teamwork. Research Objectives: This study aims to design and evaluate the effectiveness of a circuit-based team competition model to improve basic athletic techniques in primary school PE. Method: A research and development (R&D) approach was used, involving 30 purposively selected students. The model was developed through expert validation and implemented over a five-week field trial. Data were collected using expert judgment forms and a fundamental athletics skill test. A one-sample t-test was conducted to assess pretest and posttest differences. Finding/Results: The implementation of the model resulted in significant improvements in students’ athletic performance. The mean score increased from 62.4 (SD = 5.3) to 78.6 (SD = 6.1), with a statistically significant result (t = 6.24; p < 0.001). Approximately 90% of students demonstrated notable improvement. The highest gains were observed in sprinting and mini hurdles, which also showed strong instrument validity (r = 0.68–0.69). Conclusion: The circuit-based team competition model is effective in enhancing primary students’ basic athletic skills while also boosting motivation and active participation. This study offers a promising approach for improving learning strategies in physical education.